pH-mediated inhibition of a bumble bee parasite by an intestinal symbiont - Palmer-Young, Evan C (Parasitology, 2018)
Gut symbionts can augment resistance to pathogens by stimulating host immune responses, competing for space and nutrients, or producing antimicrobial metabolites. Gut microbiota of social bees, which pollinate many crops and wildflowers, protects hosts against diverse infections and might counteract pathogen-related bee declines. Bumble bee gut microbiota, and specifically abundance of Lactobacillus “Firm-5” bacteria, can enhance resistance to the trypanosomatid parasite Crithidia bombi. However, the mechanism underlying this effect remains unknown. We hypothesized that the Firm-5 bacterium Lactobacillus bombicola, which produces lactic acid, inhibits C. bombi via pH-mediated effects. Consistent with our hypothesis, Lactobacillus bombicola spent medium inhibited C. bombi growth via reduction in pH that was both necessary and sufficient for inhibition. Inhibition of all parasite strains occurred within the pH range documented in honey bees, though sensitivity to acidity varied among strains. Spent medium was slightly more potent than HCl, D-, and L-lactic acids for a given pH, suggesting that other metabolites also contribute to inhibition. Results implicate symbiont-mediated reduction in gut pH as a key determinant of trypanosomatid infection in bees. Future investigation into in vivo effects of gut microbiota on pH and infection intensity would test the relevance of these findings for bees threatened by trypanosomatids.